2021
DOI: 10.3389/fanim.2021.788930
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Impact of Glucocorticoids During Pregnancy on Muscle Development and Function

Abstract: Maternal stress, such as maternal obesity, can induce severe gestational disease and hormonal disorder which may disrupt fetal organ maturation and further cause endangered early or future health in offspring. During fetal development, glucocorticoids are essential for the maturation of organ systems. For instance, in clinical applications, glucocorticoids are commonly utilized to pregnant women with the risk of preterm delivery to reduce mortality of the newborns. However, exposure of excessive glucocorticoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 137 publications
0
1
0
Order By: Relevance
“…Evidence suggested that excessive fetal glucocorticoids would cause abnormal skeletal muscle development and cardiovascular function both in the prenatal and postnatal phases. The impact of prenatal glucocorticoids would continue over the course of a person’s life ( Liu et al, 2021 ). Convinced researchers documented that prenatal steroids would result in intrauterine growth restriction (IUGR).…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 99%
“…Evidence suggested that excessive fetal glucocorticoids would cause abnormal skeletal muscle development and cardiovascular function both in the prenatal and postnatal phases. The impact of prenatal glucocorticoids would continue over the course of a person’s life ( Liu et al, 2021 ). Convinced researchers documented that prenatal steroids would result in intrauterine growth restriction (IUGR).…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 99%